The Creation of the Universe Judging from the Naqli and Aqli Propositions - Nuril Fathurin (Journal Intellectual Sufism Research (JISR), 2022)
This study aims to determine the basis, process, interrelationship, and urgency of the creation of the universe in terms of the naqli argument. This type of research is a qualitative research with library research method , which is a series of activities related to the method of collecting library data through reading, recording and processing research data by conducting a review study of books, literatures, notes. and reports related to the problem being solved. The results of the study indicate that the basis for the creation of the universe in terms of the naqli argument is explained in the verses of the Qur'an, including QS. Al-A'raaf [7]: 54, QS. Yunus [10]: 3, QS. Hud [11]: 7, al-Hadid [57]: 4, and others. The review of the naqli arguments explains that the process of creating the universe is divided into six stages, namely the big explosion, until the creation of animals and then humans. While the review of aqli theorems in science, the beginning of the creation of the universe was put forward by the Big Bang theory , Stephen Hawking, Rasyid Ridha, Marconi, and others. There are several links between the texts and the theories that have been put forward, including the process of creating the universe which is divided into six stages, the process of creating the universe comes from something solid, the material for the formation of the universe comes from water, the material for the creation of the heavens and the earth is a kind of smoke. (dukhon) . There is a link between the process of creating the universe, reviewing the naqli (al-Qur'an) and aqli (science) propositions with the finding of compatibility with scientific evidence that answers a lot of cues from the Qur'an, so as a believer, his faith should be more and more about the existence of Allah, the truth of Islam, and the truth of the holy verses of the Qur'an.